2019
DOI: 10.1101/642827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host density dependence and environmental factors affecting laurel wilt invasion

Abstract: Host size, density and distribution, in addition to climate, can affect the likelihood a pathogen will invade and saturate landscapes. Laurel wilt, caused by the vector-borne forest pathogen Raffaelea lauricola, has devastated populations of native Lauraceae in the Southeastern US, and continues to spread. We surveyed 87 plots in six coastal islands in South Carolina, Georgia and North Florida, and one inland site (Archbold Biological Station) in South Florida for laurel wilt-affected and non-affected individu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…All "redbays" appear to be highly susceptible to laurel wilt in controlled inoculation studies [12,54,55], and in the field, widespread mortality from laurel wilt has been observed in swampbay populations [56,57]. However, silkbay is thought to be restricted to the sandhills areas of central Florida and has not been as affected by the wilt as have other native Persea taxa [58]. One reason for this may be the overall smaller average diameter of silkbay compared to other Persea taxa and therefore it is less attractive to X. glabratus and less likely to be attacked by the beetle, which tends to preferentially attack larger diameter hosts [12,28,58].…”
Section: Redbay (Persea Borbonia)mentioning
confidence: 99%
See 1 more Smart Citation
“…All "redbays" appear to be highly susceptible to laurel wilt in controlled inoculation studies [12,54,55], and in the field, widespread mortality from laurel wilt has been observed in swampbay populations [56,57]. However, silkbay is thought to be restricted to the sandhills areas of central Florida and has not been as affected by the wilt as have other native Persea taxa [58]. One reason for this may be the overall smaller average diameter of silkbay compared to other Persea taxa and therefore it is less attractive to X. glabratus and less likely to be attacked by the beetle, which tends to preferentially attack larger diameter hosts [12,28,58].…”
Section: Redbay (Persea Borbonia)mentioning
confidence: 99%
“…However, silkbay is thought to be restricted to the sandhills areas of central Florida and has not been as affected by the wilt as have other native Persea taxa [58]. One reason for this may be the overall smaller average diameter of silkbay compared to other Persea taxa and therefore it is less attractive to X. glabratus and less likely to be attacked by the beetle, which tends to preferentially attack larger diameter hosts [12,28,58].…”
Section: Redbay (Persea Borbonia)mentioning
confidence: 99%